A Cognitive Analysis of Informatics Patient Safety Issues Reported Within the Veterans Health Administration. Issue 1 (June 2015) - Chapman, Roger J.; Taylor, Lesley
The goal of the Veterans Health Administration (VHA) Informatics Patient Safety program (IPS) is to improve the safety of Health Information Technology (HIT) products. To support the analysis of patient safety issues, a set of categories was developed for Human-HIT interaction errors that can occur as users conduct their work (Chapman, Taylor, and Wood, 2012). Here we describe the categorization of 97 patient safety issues reported to IPS between October 1st 2013 and September 30th 2014. We highlight: (1) how categorization can contribute to the risk assessment process, (2) which error types were most frequently found, and (3) how these results suggest the categories and our issue analysis process can be refined.